2014
DOI: 10.3389/fpsyt.2014.00087
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Parietal Brain Function in ADHD: Replication and Extension of Previous EEG Beta Asymmetry Findings

Abstract: Background: Abundant work indicates ADHD abnormal posterior brain structure and function, including abnormal structural and functional asymmetries and reduced corpus callosum size. However, this literature has attracted considerably less research interest than fronto-striatal findings.Objective: To help address this imbalance, the current study replicates and extends our previous work showing abnormal parietal brain function in ADHD adults during the Conner’s Continuous Performance Test (CPT).Method: Our previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 128 publications
(137 reference statements)
0
25
0
Order By: Relevance
“…For instance, in a multimodal voxel‐based morphometry and functional MRI meta‐analysis, an overlapping cluster in the right putamen/anterior insula showed both decreased grey matter volume and reduced inhibition‐related activation in individuals with ADHD relative to controls, highlighting the idea that abnormal grey matter volume in the basal ganglia is related to abnormal inhibitory function. Moreover, the involvement of the corpus callosum in the pathophysiology of ADHD highlighted in DTI studies has also been demonstrated in volumetric and functional studies …”
Section: Structural Brain Imaging In Adhdmentioning
confidence: 84%
See 1 more Smart Citation
“…For instance, in a multimodal voxel‐based morphometry and functional MRI meta‐analysis, an overlapping cluster in the right putamen/anterior insula showed both decreased grey matter volume and reduced inhibition‐related activation in individuals with ADHD relative to controls, highlighting the idea that abnormal grey matter volume in the basal ganglia is related to abnormal inhibitory function. Moreover, the involvement of the corpus callosum in the pathophysiology of ADHD highlighted in DTI studies has also been demonstrated in volumetric and functional studies …”
Section: Structural Brain Imaging In Adhdmentioning
confidence: 84%
“…Moreover, the involvement of the corpus callosum in the pathophysiology of ADHD highlighted in DTI studies has also been demonstrated in volumetric and functional studies. 3,53 The effect of age in interpreting brain abnormalities…”
Section: Relationship Between Structural and Functional Neuroimaging mentioning
confidence: 99%
“…This effect is strong in controls, but it is absent in our ADHD group, thus suggesting that the kind of WMT performed by our group of patients only confers benefits for those tasks that were trained [15,62,113]. We could speculate that a deficit in transfer effects associated with WM training could be associated with the abnormal parietal brain function observed in ADHD [114].…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, ADHD as a single diagnostic indicator occurs in less than 20% of the cases, or even less (Barkley & Brown, 2008;Yaryura-Tobias, Rabinowitz, & Neziroglu, 2003). There has been an increasing discourse over neurofeedback techniques and outcomes using sham/placebo-controlled methods yet the aforementioned difficulties remain everpresent Gevensleben et al, 2014;Guez et al, 2015;Hale et al, 2014;Lenartowicz & Loo, 2014;Loo, Lenartowicz, & Makeig, 2015;Micoulaud-Franchi et al, 2014;Polanczyk et al, 2007;Pritchard et al, 2012;Steiner, Frenette, Rene, Brennan, & Perrin, 2014;van Dongen-Boomsma, Vollebregt, Slaats-Willemse, & Buitelaar, 2013;Vollebregt, van Dongen-Boomsma, Buitelaar, & Slaats-Willemse, 2013). Current problems, diagnostic issues, and recommendations for a concise, standard set of metrics and interventions will be presented and discussed.…”
Section: Robert Boddingtonmentioning
confidence: 99%